Unemployment Reduction in Canada: Lessons from Japan and Sweden - Harcourt, J. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1996)
The active labour market policy has been used to reduce the duration of unemployment in Sweden. The lifetime employment System has been used to lower the incidence of unemployment in Japan. Will the adoption of similar policies in Canada produce comparable reductions in unemployment? Emulating Japan and Sweden could prove difficult, since their policies reflect and reinforce employment interests that are uery different from Canada's. As a result, neither lifetime employment nor active labour market policy is transferable to Canada without major modifications to suit the stakeholder interests of Canadian unions, employers, and employees.